An economic analysis of the differences in responses and help-seeking behavior of women victims of spousal violence in the Philippines. - Kalaw, Angelo Paolo Trinidad; Nieto, Andrew Prado (2012)
This paper analyses the behavior of Women victims of spousal violence in the Philippines, and the determinants and factors affecting their decision to respond or seek help. Using the 2008 Philippine National Demographic and Health Survey, we model the response behavior of women victims to be a random utility maximization problem in which they face a set of discrete and unordered strategy alternatives that have different expected utilities and level of appropriateness to their experience of domestic violence. Results of our multinomial logit regression reveal that women’s decision and differences in their response and help-seeking behavior are affected by their socioeconomic characteristics; the marital capital of her relationship; and the kind, combination, and consequences of the violence. The results also reveal that women seek third-party intervention not based on the experience of violence per se but on the materiality and tangibility of consequences sustained. From our regression results, we provided inputs to the implementation of Republic Act 9262 in order to better help women cope with, adjust to, defend themselves, and recover from domestic violence.
Keywords: Wife abuse -- Economic aspects; Family violence -- Economic aspects